Image and Video for Hearing Impaired People. (17th April 2008) - Caplier, Alice; Stillittano, Sébastien; Aran, Oya; Akarun, Lale; Bailly, Gérard; Beautemps, Denis; Aboutabit, Nouredine; Burger, Thomas
Abstract : We present a global overview of image- and video-processing-based methods to help the communication of hearing impaired people. Two directions of communication have to be considered: from a hearing person to a hearing impaired person and vice versa. In this paper, firstly, we describe sign language (SL) and the cued speech (CS) language which are two different languages used by the deaf community. Secondly, we present existing tools which employ SL and CS video processing and recognition for the automatic communication between deaf people and hearing people. Thirdly, we present the existing tools for reverse communication, from hearing people to deaf people that involve SL and CS video synthesis.